Cross‐national comparison of social isolation and mortality among older adults: A 10‐year follow‐up study in Japan and England. Issue 2 (21st December 2020) - Saito, Masashige; Aida, Jun; Cable, Noriko; Zaninotto, Paola; Ikeda, Takaaki; Tsuji, Taishi; Koyama, Shihoko; Noguchi, Taiji; Osaka, Ken; Kondo, Katsunori
Abstract : Aim: Existing evidence links social isolation with poor health. To examine differences in the mortality risk by social isolation, and in socio‐economic correlates of social isolation, we analyzed large‐scale cohort studies in Japan and England. Methods: Participants were drawn from the Japan Gerontological Evaluation Study (JAGES) and the English Longitudinal Study of Ageing (ELSA). We analyzed the 10‐year mortality among 15 313 JAGES participants and 5124 ELSA respondents. Social isolation was measured by two scales, i.e., scoring the frequency of contact with close ties, and a composite measurement of social isolation risk. We calculated the population attributable fraction, and Cox regression models with multiple imputations were used to estimate hazard ratios (HRs) for mortality due to social isolation. Results: The proportion of those with contact frequency of less than once a month was 8.5% in JAGES and 1.3% in ELSA. Males, older people, those with poor self‐rated health, and unmarried people were significantly associated with social isolation in both countries. Both scales showed that social isolation among older adults had a remarkably higher risk for premature death (less frequent contact with others in JAGES: hazard ratio [HR] = 1.18, 95% confidence interval [CI]: 1.05–1.33, in ELSA: HR = 1.27, 95% CI: 0.85–1.89; and high isolation risk score in JAGES: HR = 1.30, 95% CI: 1.12–1.50, in ELSA: HR = 2.05, 95% CI: 1.52–2.73). The population attributable fraction showed less frequent contact with close ties was attributed to about 18 000 premature deaths annually in Japan, in contrast with about 1800 in England. Conclusions: Negative health impacts of social isolation were higher among older Japanese compared with those in England. Geriatr Gerontol Int 2021; 21: 209–214 .